Risk practices and immunization against hepatitis B among female sex workers - Rosilane de Lima Brito Magalhães; Vanessa Moura Carvalho; Giselle Mary Ibiapina Brito; Layze Braz de Oliveira; Marli Teresinha Gimeniz Galvão; Elucir Gir (Universidade Federal do Ceará, 2016)
Objective: to identify the use of hepatitis B vaccine and risk practices among female sex workers. Methods: cross-sectional research using the Respondent Driven Sampling methodology. One-hundred and fifty-three sex workers were studied.Results: risk practices were related to the early onset of sexual activity, multiple partners with up to 17 clients per week 34 (22.2%), lack of use of condom 9 (5.9%), 124 (81.0%) shared sharps and 53 (34.6%) reported no vaccine against hepatitis B. Conclusion: sex workers found themselves exposed to various risk situations to the hepatitis B virus, due to the lack of immunization schedule, sexual precocity, multiple sex partners lack of use of condom, habit of sharing sharp objects. It is urgent to invest in health promotion with guidance on the importance of the vaccine, the adoption of protective measures and increased access of sex workers to health facilities.